2014
DOI: 10.1590/1517-86922014200601814
|View full text |Cite
|
Sign up to set email alerts
|

Efeito do treinamento sobre a eficiência ventilatória de indivíduos saudáveis

Abstract: RESUMOIntrodução: Diversos índices de eficiência ventilatória (EV) têm fornecido uma medida extra para avaliação do condicionamento cardiorrespiratório em adição ao consumo de oxigênio (VO 2 ) no pico do exercício e no nível do limiar ventilatório (VO 2 LV). Em indivíduos com insuficiência cardíaca já foi demonstrado que há aumento da EV após treinamento. No entanto, a sensibilidade dessa medida para avaliar o efeito do treinamento em indivíduos saudáveis foi pouco estudada. Objetivo: Testar a hipótese de que … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 30 publications
0
2
0
1
Order By: Relevance
“…However, in this study, a positive correlation was found between this variable and the test duration in the pre-competitive phase. Therefore, it is recommended to monitor it during training, as suggested by Sauer, Pérez, and Cartelli (24). It should be noted that these authors reported weak correlations between VE/VCO 2 and VO 2 , based on previous studies.…”
Section: Discussionmentioning
confidence: 96%
“…However, in this study, a positive correlation was found between this variable and the test duration in the pre-competitive phase. Therefore, it is recommended to monitor it during training, as suggested by Sauer, Pérez, and Cartelli (24). It should be noted that these authors reported weak correlations between VE/VCO 2 and VO 2 , based on previous studies.…”
Section: Discussionmentioning
confidence: 96%
“…No obstante, en este estudio se halló una correlación positiva entre esta variable medida en el esfuerzo máximo y la duración de la prueba en la fase precompetitiva, lo cual sugiere una asociación entre la ventilación y el rendimiento. Por esta razón se recomienda monitorearla en el entrenamiento, como lo sugieren Sauer, Pérez y Cartelli (26), quienes sostienen que el equivalente ventilatorio para dióxido de carbono puede ser medido en las diferentes fases de la ergoespirometría, lo cual implica que pueda ser medido en el momento en que se alcanza el VO 2máx. , como se realizó en este estudio .…”
Section: Discussionunclassified
“…Incorporating three discrete exercise protocols, specifically aerobic, resistance, and flexibility training, has effectively mitigated pain and fatigue symptoms. The observed improvement in cardiorespiratory function in combined exercise training programs can be attributed to the synchronization of ventilation-perfusion and the oxidative capacity of skeletal muscle [ 75 , 76 ].…”
Section: Physical Exercises and Breast Cancer Treatmentmentioning
confidence: 99%